Preparation and characterization of surface magneto-optic kerr effect (smoke) in strontium ferrite (SrFe12O19) via sol-gel route / N. Yahya … [et al.] - Yahya, N.; Azhan, H.; Hashim, M.; Hari, Z.; Aziz, R. S.; Saiden, N. M.; Hasan, H. (2002)
Surface Magneto-Optic Kerr Effect (SMOKE) measurements performed on polycrystalline SrFe12019 ferrites was obtained using an applied field of = 0.4 Tesla and at a temperature of 300 K temperature. In this project, strontium hexaferrites were prepared by the chemical sol-gel route to get fine, pure and homogeneous of powders. Ferum Nitrate Hexahidrate, Fe(NO3) 3- 6H20 and Strontium Nitrate, Sr(NO2)3 were dissolved in citric acid solution by using a magnetic stirrer. The solution was slowly evaporated until a gel was formed after 2 weeks. This gel was dried at 110 °C in an oven for 2 days. The powders were analyzed by using X-ray Diffraction at various temperatures (800 °C, 900 °C and 1000 °C) to confirm the formation of the strontium ferrite phase. These powders were then presintered at 800 °C for 3 hours. After that, the powders were sieved and were mixed with PVA liquid as a binding agent before being moulded into pellet shape. The samples were sintered at 950 °C and 1000 °C for 3 hours in air. From the results, it was found that the formation of SrFe12O19 phase occurs at 1000 °C. In conclusion, the both SrFe12O19 (sintered at 950 °C and 1000 °C) showed Kerr rotation, ΨKerr about 1.1° and 1.5°, respectively.